Capital inflow, growth sustainability and financial debacles - Ghosh, B. N. (My University, 2003)
The present paper is a phenomenological study of capital inflow, economic growth and financial crisis in the Southeast Asian countries in general and Malaysia in particular. The paper seeks to explain how unregulated capital inflow in an open economy leads to unsustainable growth It comes to the broad conclusion that although capital inflow is conducive to economic growth, it may also generate the problem of macroeconomic vulnerability and unsustainability, and in such a situation, the occurrence of financial crisis may not be an uncommon possibility. © MCB UP Limited 2003.
Keywords: Accounting research; Crisis; Economic growth; Foreign investment; Malaysia